Real‑life cost‑effectiveness of benralizumab in patients with severe asthma. - Padilla‑Galo, A.; García-Ruiz, Antonio J.; Levy Abitbol, R. Ch.; Olveira-Fuster, Casilda; Rivas‑Ruiz, F; García-Agua-Soler, Nuria; Pérez Morales, Marcel; Valencia Azcona, B.; Tortajada‑Goitia, B.; Moya‑Carmona, Isabel; Levy‑Naon, Alberto (BMC, 2021)
The aim of this study was to evaluate clinical outcomes and healthcare expenditure after incorporating benralizumab into the standard treatment of refractory eosinophilic asthma. Methods: This was a cross-sectional multicentre study of consecutive patients with refractory eosinophilic asthma who received treatment with benralizumab during at least 12 months. Patient follow-up was performed in specialised severe asthma units. The main effectiveness parameters measured were: the avoidance of one asthma exacerbation, a 3-point increase in the asthma control test (ACT) score, and the difference in utility scores (health-related quality of life) between a 1-year baseline treatment and 1-year benralizumab treatment. The health economic evaluation included direct costs and incremental cost-effectiveness ratios (ICERs). Results: After 1 year of treatment with benralizumab, patients with refractory eosinophilic asthma showed an improvement in all the effectiveness parameters analysed: improvement of asthma control and lung function, and decrease in the number of exacerbations, oral corticosteroid (both as corticosteroid courses and maintenance therapy), and inhaled corticosteroid use. The total annual cost per patient for the baseline and benralizumab treatment periods were €11,544 and €14,043, respectively, reflecting an increase in costs due to the price of the biological agent but a decrease in costs for the remaining parameters. The ICER was €602 per avoided exacerbation and €983.86 for every 3-point increase in the ACT score. Conclusions: All the pharmacoeconomic parameters analysed show that treatment with benralizumab is a costeffective option as an add-on therapy in patients with refractory eosinophilic asthma.
CC BY
Keywords: Asma - Tratamiento - Aspectos económicos; Anticuerpos monoclonales - Uso terapéutico - Aspectos económicos; Asthma; Benralizumab; Cost-effectiveness; Eosinophils